2011
DOI: 10.4049/jimmunol.1003337
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Coding Single Nucleotide Polymorphisms of Endoplasmic Reticulum Aminopeptidase 1 Can Affect Antigenic Peptide Generation In Vitro by Influencing Basic Enzymatic Properties of the Enzyme

Abstract: ER aminopeptidase 1 (ERAP1) customizes antigenic peptide precursors for MHC class I presentation and edits the antigenic peptide repertoire. Coding single nucleotide polymorphisms (SNPs) in ERAP1 were recently linked with predisposition to autoimmune disease, suggesting a link between pathogenesis of autoimmunity and ERAP1-mediated Ag processing. To investigate this possibility, we analyzed the effect that disease-linked SNPs have on Ag processing by ERAP1 in vitro. Michaelis–Menten analysis revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(185 citation statements)
references
References 19 publications
9
171
2
3
Order By: Relevance
“…This observation is in accordance with a previous study showing that charged N-terminal residues were relatively protected from ERAP1 degradation (35). In vitro studies using synthetic peptides have shown that ERAP1 polymorphisms have substrate-dependent effects on enzyme activity (7,(36)(37)(38). A recent cell-based study showed that protective ERAP1 polymorphisms resulted in increased length and altered P1 residues of peptides bound to HLA-B*27:04 (39).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in accordance with a previous study showing that charged N-terminal residues were relatively protected from ERAP1 degradation (35). In vitro studies using synthetic peptides have shown that ERAP1 polymorphisms have substrate-dependent effects on enzyme activity (7,(36)(37)(38). A recent cell-based study showed that protective ERAP1 polymorphisms resulted in increased length and altered P1 residues of peptides bound to HLA-B*27:04 (39).…”
Section: Discussionsupporting
confidence: 92%
“…This could make the two molecules differently prone to exchange peptides in the TGN where they can encounter a set of tissue-specific peptides different from those generated by the classical proteasomal machinery. Ultimately, the rate of peptide exchange will be influenced by the repertoire of peptides generated in the ER, which in turn depends on the trimming activity of ERAP1 that changes according to the allelic variants, some of which are strongly associated with AS (17,43).…”
Section: Discussionmentioning
confidence: 99%
“…The most common protein variants, reported as ERAP1 allotypes, are encoded by haplotypes created by missense variant combinations of SNPs harboured in an ancestral haplotype found in humans as well as in primates [78]. The most investigated ERAP1 allotypes (from 10 to 13) [78,79] are distinguished by enzymatic functions with both qualitative (substrate preferences) and quantitative (high, intermediate and low activity variants) effects [5,64,[80][81][82]. Interestingly, some non-synonymous SNPs influence the gene expression level of ERAP1 [83].…”
Section: Hla-b27 a Molecule With Two Faces: Protection From Viral Inmentioning
confidence: 99%